Red blood cell alloimmunization in neonates and children up to 3 years of age. Issue 11 (6th September 2017) - Türkmen, Tugce; Qiu, Dan; Cooper, Nina; Sachs, Ulrich J.; Wößmann, Wilhelm; Schranz, Dietmar; Zimmer, Klaus‐Peter; Ehrhardt, Harald; Hackstein, Holger; Bein, Gregor
Abstract : BACKGROUND: An alloimmune response to red blood cell (RBC) transfusion in neonates is a rare event. Several guidelines recommend limited pretransfusion testing in neonates. The evidence for these recommendations is based on small studies with sample sizes of between 30 and 90 infants. STUDY DESIGN AND METHODS: We conducted a retrospective cohort study among consecutive patients who received transfusions at a single university medical center. All non‐alloimmunized patients who had received their first RBC transfusion between 1994 and 2013 and who underwent at least one antibody screening follow‐up visit between 7 and 365 days after transfusion were included. RESULTS: The incidence of alloimmunization in the control group of 17, 084 adult patients age 45 years or older who had received a median of 5 RBC units (interquartile range, 2‐12 RBC units) was 3.55% (n = 607 alloimmunized patients). After transfusion of 40 RBC units, the cumulative incidence of alloimmunization in adult controls was 10.24% (95% confidence interval, 7.71%‐13.17%). In total, 1641 neonates and children up to age 3 years received a median of 4 RBC units (interquartile range, 2‐7 RBC units) in a median of two RBC transfusion episodes (interquartile range, one to five RBC transfusion episodes). Two children developed anti‐M and anti‐E antibodies post‐transfusion at the ages of 181 and 611 days, respectively. CONCLUSION: To our knowledge, this study presents the largest longitudinal cohort study of RBC alloimmunization in neonates. Antibodies against RBC antigens were not detected within the first 6 months of life. Repeat antibody screening and cross‐matching during the first months of life can be safely omitted.